The role of the noradrenergic system in the exploration-exploitation trade-off: a pharmacological study - Jepma, Marieke; Te Beek, Erik T.; Wagenmakers, Eric-Jan; Van Gerven, Joop M.; Nieuwenhuis, Sander (Frontiers in Human Neuroscience, 2010)
Animal research and computational modeling have indicated an important role for the neuromodulatory locus coeruleus-norepinephrine (LC-NE) system in the control of behavior. According to the adaptive gain theory, the LC-NE system is critical for optimizing behavioral performance by regulating the balance between exploitative and exploratory control states. However, crucial direct empirical tests of this theory in human subjects have been lacking. We used a pharmacological manipulation of the LC-NE system to test predictions of this theory in humans. In a double-blind parallel-groups design (N = 52), participants received 4 mg reboxetine (a selective norepinephrine reuptake inhibitor), 30 mg citalopram (a selective serotonin reuptake inhibitor) or placebo. The adaptive gain theory predicted that the increased tonic NE levels induced by reboxetine would promote task disengagement and exploratory behavior. We assessed the effects of reboxetine on performance in two cognitive tasks designed to examine task (dis)engagement and exploitative versus exploratory behavior: a diminishing-utility task and a gambling task with a non-stationary pay-off structure. In contrast to predictions of the adaptive gain theory, we did not find differences in task (dis)engagement or exploratory behavior between the three experimental groups, despite demonstrable effects of the two drugs on non-specific central and autonomic nervous system parameters. Our findings suggest that the LC-NE system may not be involved in the regulation of the exploration-exploitation trade-off in humans, at least not within the context of a single task. It remains to be examined whether the LC-NE system is involved in random exploration exceeding the current task context.